ANALISIS PERBANDINGAN PENURUNAN PONDASI TIANG PANCANG TUNGGAL METODE EMPIRIS DAN PROGRAM PLAXIS 2D V8.6 - Reny Pradista; Fatmawati, laily Endah (DPPM Universitas Pelita Bangsa, 2024)
The main purpose of the foundation is to be able to accept the load from above and to fulfill this goal the foundation must fulfill the criteria of decline or decrease that should [1]. To be able to calculate the prediction of decline, this study uses the empirical method of Vesic 1970 and program assistance (software). Also calculated for the value of the foundation permit reduction. The data used are secondary data in the form of pile data, PDA (Pile Driving Analyzer) test result data, SPT (Standard Penetration Test) soil investigation data. The axial load used is the allowable load from the planner data based on the soil investigation point point 2 of 796.6 kN. From the results of the analysis, it was found that the value that exceeded the results of the PDA (Pile Driving Analyzer) test was the calculation result from the 1970 Vesic method of 8.5mm, while the result of the decrease from the PDA (Pile Driving Analyzer) test was 4-5 mm.